Binuclear cyclopalladated compounds with antitubercular activity: synthesis and characterization of [{Pd(C-2,N-dmba)(X)}(2)(mu-bpp)] (X = Cl, Br, NCO, N-3; bpp=1,3-bis(4-pyridyl)propane) - Moro, Antonio C. [UNESP]; Urbaczek, Ana C. [UNESP]; De Almeida, Eduardo T.; Pavan, Fernando R. [UNESP]; Leite, Clarice Q. F. [UNESP]; Netto, Adelino Vieira de Godoy [UNESP]; Mauro, Antonio Eduardo [UNESP] (Taylor & Francis Ltd, 2012)
Reactions between [Pd(C-2,N-dmba)(mu-X)](2) (Hdmba = N,N-dimethylbenzylamine; X = Cl, Br, NCO, N-3) and 1,3-bis(4-pyridyl)propane (bpp) in 1 : 1 molar ratio at room temperature resulted in the binuclear compounds [{Pd(C-2,N-dmba)(X)}(2)(mu-bpp)] (X = Cl (1), Br (2), NCO (3), N-3 (4)), which were characterized by elemental analyses, infrared (IR), H-1- and C-13{H-1}-NMR spectroscopies, and thermogravimetric analysis. The IR and NMR data of 1-4 were consistent with the presence of bridging bpp. The thermal stability order of the complexes was 4 > 3 > 2 > 1. Compounds 1-4 and bpp were tested against Mycobacterium tuberculosis and their MIC values were determined.
Keywords: Cyclopalladated; bpp; Spectroscopy; Tuberculosis; Antimycobacterial agents